2016
DOI: 10.1016/j.jpeds.2016.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Relative Age on Diagnosis and Treatment of Attention-Deficit Hyperactivity Disorder in Taiwanese Children

Abstract: Relative age, as an indicator of neurocognitive maturity, is crucial in the risk of being diagnosed with ADHD and receiving ADHD medication among children and adolescents. Our findings emphasize the importance of considering the age of a child within a grade when diagnosing ADHD and prescribing medication for treating ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 18 publications
3
47
1
2
Order By: Relevance
“…3 Although this study confirms a relative age effect, there have been mixed findings from other countries with low prescribing rates. [14][15][16][17] It is possible that this discrepancy reflects our specific focus on the receipt of ADHD diagnosis whereas studies from Nordic countries which did not find a consistent relative age effect used medication data as the ADHD outcome. 14,15 In both boys and girls, we found a greater cumulative incidence of clinically diagnosed ADHD amongst younger children within the school-year.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…3 Although this study confirms a relative age effect, there have been mixed findings from other countries with low prescribing rates. [14][15][16][17] It is possible that this discrepancy reflects our specific focus on the receipt of ADHD diagnosis whereas studies from Nordic countries which did not find a consistent relative age effect used medication data as the ADHD outcome. 14,15 In both boys and girls, we found a greater cumulative incidence of clinically diagnosed ADHD amongst younger children within the school-year.…”
Section: Discussionmentioning
confidence: 87%
“…12,13 In contrast, there are mixed findings from large-scale studies from Nordic countries (such as Denmark and Sweden) and Taiwan where the prevalence rates of ADHD treatment in children are lower. [14][15][16][17] Hence, it is possible that a relative age effect may partially be an artefact of national patterns in the recognition and treatment of ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies on the subject have been from Western and developed/high income countries. In a notable exception, a study from Taiwan showed similar results, suggesting that the association between younger age and ADHD diagnosis may be seen also in other cultures (Chen, Lan, Bai et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Their analyses revealed a relative age effect in the diagnosis ADHD, meaning that boys who were born in December were 30% more likely to receive a diagnosis of ADHD than boys born in January, while girls born in December were 70% more likely to receive a diagnosis than girls born in January (December 31 was the annual cutoff date of birth for entry to school in British Columbia). Four recent, independent of each other studies conducted in different countries (Taiwan, Turkey, Spain, and Germany) have also come to the conclusion that the probability of displaying ADHD symptoms is greater among children who begin school at an earlier age (Librero et al, 2015;Chen et al, 2016;Schwandt and Wuppermann, 2016;Gökçe et al, 2017). As Furman (2005) has concisely articulated it "ADHD is not a disease per se but rather a group of symptoms representing a final common behavioral pathway for a gamut of emotional, psychological, and/or learning problems" (p. 994).…”
mentioning
confidence: 95%